2012
DOI: 10.1017/s1355770x12000137
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and the measurement of wealth

Abstract: We develop and apply a consistent and comprehensive theoretical framework for assessing whether economic growth is compatible with sustaining wellbeing over time. Our approach differs from earlier approaches by concentrating on wealth rather than income. Sustainability is demonstrated by showing that a properly defined comprehensive measure of wealth is maintained through time. Our wealth measure is unusually comprehensive, capturing not only reproducible and human capital but also natural capital, health impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
478
0
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 539 publications
(503 citation statements)
references
References 27 publications
(42 reference statements)
6
478
0
19
Order By: Relevance
“…It is traditionally measured by the "net capital stock" [which is termed "net stock" by the US Bureau of Economic Analysis (BEA)] of fixed assets owned by private business, nonprofit institutions, and government, plus the net stock of durable goods owned by consumers (3,4). In the context of developing indictors for measuring sustainability, there have been efforts (5)(6)(7)(8) in recent years to provide a more comprehensive measurement of wealth by taking into account stocks of additional forms of capital (e.g., natural and human capital). These efforts remind us that there are linkages between manufactured and natural capital [which is a stock that includes land, water, forests, minerals, solar energy, fossil fuels, living organisms, and the services provided by the interactions of all of these elements in ecological systems (5)(6)(7)(8)(9)].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is traditionally measured by the "net capital stock" [which is termed "net stock" by the US Bureau of Economic Analysis (BEA)] of fixed assets owned by private business, nonprofit institutions, and government, plus the net stock of durable goods owned by consumers (3,4). In the context of developing indictors for measuring sustainability, there have been efforts (5)(6)(7)(8) in recent years to provide a more comprehensive measurement of wealth by taking into account stocks of additional forms of capital (e.g., natural and human capital). These efforts remind us that there are linkages between manufactured and natural capital [which is a stock that includes land, water, forests, minerals, solar energy, fossil fuels, living organisms, and the services provided by the interactions of all of these elements in ecological systems (5)(6)(7)(8)(9)].…”
mentioning
confidence: 99%
“…In the context of developing indictors for measuring sustainability, there have been efforts (5)(6)(7)(8) in recent years to provide a more comprehensive measurement of wealth by taking into account stocks of additional forms of capital (e.g., natural and human capital). These efforts remind us that there are linkages between manufactured and natural capital [which is a stock that includes land, water, forests, minerals, solar energy, fossil fuels, living organisms, and the services provided by the interactions of all of these elements in ecological systems (5)(6)(7)(8)(9)]. From an industrial ecology perspective, one of these linkages is that the formation and operation of manufactured capital requires the transfer of physical materials from natural capital to manufactured capital, such as from iron ores to iron metal and then to components of automobiles.…”
mentioning
confidence: 99%
“…Indeed, individuals in our case study have been found to be willing to substitute, to some extent, some level of environmental quality if the level of waiting time was lower and the availability of other forms of natural capital was higher. Whilst uncertainty over future environmental impacts and a lack of discounting of very long run benefits versus long run benefits can both be interpreted as not fitting within the standard model of weak sustainability (eg Arrow et al 2012), note that we have not tested whether variations in time-specific valuations can be linked to individual perceptions over the substitutability of different forms of capital (eg natural for human) or the perceptions of future environmental risks.…”
Section: Discussionmentioning
confidence: 99%
“…By widening the range of capital assets to include health, education, and natural capital, the theory I am recounting here extends the notion of capital. So we are obliged to stretch the 2 See Hamilton and Clemens (1999), Dasgupta and Mäler (2000), Arrow et al (2003Arrow et al ( , 2004Arrow et al ( , 2012a, Dasgupta (2004Dasgupta ( , 2009, and UNU-IHDP/UNEP (2012). 3 The theory shows that even the previous sentence in the text requires explanation: Let L(t) denote population size at date t, K i (t) the stock of capital asset i, and P i (t) the asset's shadow price.…”
Section: What Is Investment?mentioning
confidence: 99%